2005
DOI: 10.1051/0004-6361:20053039
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly damped fast MHD kink modes in longitudinally stratified tubes with thick non-uniform transitional layers

Abstract: Abstract.Resonantly damped fast kink quasi-modes are computed in fully resistive magnetohydrodynamics (MHD) for twodimensional equilibrium models. The equilibrium model is a straight cylindrically symmetric flux tube with a plasma density that is non-uniform both across and along the loop. The non-uniform layer across the loop is not restricted to be thin, but its thickness can reach values up to the loop diameter. Our results indicate that the period and damping of coronal loop oscillations mainly depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 30 publications
10
68
0
Order By: Relevance
“…This damping time has been tested numerically by Steinolfson & Davila (1993). In addition, Poedts & Kerner (1991) and Arregui et al (2005) found that the damping rate is independent of the magnetic diffusivity (although this is only true for resonant absorption). Comparing the two systems (i.e., Figs.…”
Section: Discussionmentioning
confidence: 99%
“…This damping time has been tested numerically by Steinolfson & Davila (1993). In addition, Poedts & Kerner (1991) and Arregui et al (2005) found that the damping rate is independent of the magnetic diffusivity (although this is only true for resonant absorption). Comparing the two systems (i.e., Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Pascoe et al 2007a), although it is beyond the scope of the present paper. Calculations by Van Doorsselaere et al (2004) and Arregui et al (2005) suggest that the effect of the finite inhomogeneous layer on the period of oscillation can be important for 1, and so might be relevant for our loops 1 and 2. Yu et al (2015) also show that the choice of density profile in the inhomogeneous layer has a small effect on the period of oscillation for standing kink modes in magnetic slabs.…”
Section: Dispersion Diagramsmentioning
confidence: 91%
“…To model this loop multi-thread structure, Terradas et al (2008) has numerically solved the initial value problem and found that the process of resonant absorption was still an efficient damping mechanism in more complex and realistically structured loop models (see also the work of Ofman 2005). Further study into the properties of standing kink waves has also been undertaken relating plasma inhomogeneity in the direction of the magnetic field caused by, e.g., density (Díaz et al 2004;Andries et al 2005b;Arregui et al 2005;Dymova & Ruderman 2006;Verth et al 2007) or magnetic Ruderman et al 2008) stratification. It was shown that eigenfrequencies and eigenfunctions of coronal loops with longitudinal stratification were altered in such a way that one could determine, e.g., the coronal density scale height by estimating the ratio of the fundamental mode to that of higher overtones, a technique first proposed by Andries et al (2005a) and later developed by to correct for magnetic stratification.…”
Section: Introductionmentioning
confidence: 99%